The spontaneous mutation rate of Drosophila pseudoobscura - Krasovec, Marc (G3 : genes - genomes - genetics, 2021)
The spontaneous mutation rate is a very variable trait that is subject to drift, selection and is sometimes highly plastic. Consequently, its variation between close species, or even between populations from the same species, can be very large. Here, I estimated the spontaneous mutation rate of Drosophila pseudoobscura and Drosophila persimilis crosses to explore the mutation rate variation within the Drosophila genus. All mutation rate estimations in Drosophila varied fourfold, probably explained by the sensitivity of the mutation rate to environmental and experimental conditions. Moreover, I found a very high mutation rate in the hybrid cross between D. pseudoobscura and D. persimilis, in agreement with known elevated mutation rate in hybrids. This mutation rate increase can be explained by heterozygosity and fitness decrease effects in hybrids.